Unintended effects of urbanization in China: Land use spillovers and soil carbon loss - Li, Man; Wu, JunJie; Deng, Xiangzheng (International Food Policy Research Institute, 2011)
This paper uses a national-level geographic information system database on land use, weather conditions, land quality, soil organic carbon (SOC), topographic features, and economic variables to analyze the major drivers of land use change and the resulting impact on soil carbon storage in China. The framework developed in this study includes two main components. One is a spatial panel multinomial logit land use model that takes into account the spatial and temporal dependence of land use choices explicitly. The other is a statistical causal evaluation model that estimates the effect of land use change on SOC density. Results indicate that local economic growth, as measured by county-level gross domestic product, was a major cause of urban development and grassland conversions. Rapid expansion of road networks, promoted by massive public investment, increased the conversion of forests, grassland, and unused land to crop production and urban development. Urbanization had significant secondary ripple effects in terms of both indirect land use change and soil carbon loss. Some of the soil carbon loss may be irreversible, at least in the short run.